Polygonal evolution of wheels and its effect on vehicle dynamics - XU Hui; SONG Dongli; TIAN Guangrong (机车电传动)
The polygonal evolution of wheels affects the operational safety of EMUs. In order to study the evolution process and its effect on vehicle vibration behaviors, the wheel profile of an EMU in China was measured and analyzed. Based on the vehicle dynamics theory and rolling contact theory, a vehicle-rail coupling dynamics model was established, and the characteristics of polygonal wear were simulated from angles of view of the time domain and frequency domain. Assuming that the lateral wheel profile and nominal wheel radius were unchanged, a long-term wear iterative model was established in combination with the USFD wear model, to simulate the polygonal evolution behaviors, and the effect on the dynamic performance was analyzed on the basis of the measured out-of-roundness data. The results show that there is a phase difference between the final circumferential profile and the initial profile, and the waveform changes little with worsening wheel wear. The wheel polygon has little effect on the running stability index, but it affects the wheel-rail dynamic interaction. The maximum wheel-rail vertical force decreases with the increase of wheel out-of-roundness wavelength, and increases with the increase of speed and roughness amplitude. At the same driving speed, the vertical acceleration amplitude of the frame increases with the increase of the roughness amplitude.